Design and Fabrication of a Low-Cost, Multiband and High Gain Square Tooth-Enabled Metamaterial Superstrate Microstrip Patch Antenna - Khaled Aliqab; Sunil Lavadiya; Meshari Alsharari; Ammar Armghan; Malek G. Daher; Shobhit K. Patel (Micromachines, 2023)
The manuscript represents a novel square tooth-enabled superstrate metamaterial loaded microstrip patch antenna for the multiple frequency band operation. The proposed tooth-based metamaterial antenna provides better gain and directivity. Four antenna structures are numerically investigated for the different geometry of the patch and tooth. These proposed structures are simulated, fabricated, measured, and compared for the frequency range of 3 GHz to 9 GHz. The electrical equivalent model of the split-ring resonator is also analyzed in the manuscript. The comparative analysis of all of the proposed structures has been carried out, in terms of several bands, reflectance response, VSWR, gain and bandwidth. The results are compared with previously published works. The effects are simulated using a high-frequency structure simulator tool with the finite element method. The measured and fabricated results are compared for verification purposes. The proposed structure provides seven bands of operation and 8.57 dB of gain. It is observed that the proposed design offers the multiple frequency band operation with a good gain. The proposed tooth-based metamaterial antenna suits applications, such as the surveillance radar, satellite communication, weather monitoring and many other wireless devices.